Shear tests for characterization of bituminous mixtures stiffness - Pereira, Paulo A. A. (1997)
This paper presents the results of a study where the shear stiffness and the shear phase angle of bituminous mixtures, with two different air-void contents and three different bitumen contents were measured using shear strain controlled tests. The shear tests were carried out at three temperatures, 4, 20 and 40 ºC, and 10, 5, 2, 1, 0.5, 0.2 and 0.1 Hz frequencies were used, in agreement with SHRP M-003 specification. The specified strain level of 0.0001 mm/mm was used beside two more strain levels, 0.0002 mm/mm and 0.0005 mm/mm. With this study a shear behaviour comparison between mixtures with two air void contents, three bitumen contents was carried out at three test temperatures, seven frequencies and three strain levels. Five replicates for the main mixture and two replicates for the other mixtures were used. A total number of 693 shear tests were performed.